Introgression of root trait genes for drought tolerance to a Malaysian rice variety by marker-assisted backcross breeding - Ab Jalil, Masitah; Juraimi, Abdul Shukor; Yusop, Mohd Rafii; Uddin, Md Kamal; Hakim, Md Abdul (Friends Science Publishers, 2018)
Drought gives a huge impact in declining rice yield. To overcome this problem, rice variety with ability to withstand limited water availability need to be developed. The study was conducted to introgress root trait genes from aerobic rice variety, AERON1, to a high yielding rice variety of Malaysia, MRQ74, through marker-assisted backcross breeding (MABC). Two foreground markers, RM242 and RM263, and 57 background markers were used along the breeding program. The Chi-square (χ²) analysis showed a good fit to the expected segregation ratio (1:1) for a single dominant gene model (d.f. =1, P > 0.05) for both foreground markers. The Chi-square values in BC1F1 and BC2F1, for RM242 and RM263 were χ²=3.1 and χ²=0.03, and χ²=1.01 and χ²=0.22, respectively. The recurrent parent genome (RPG) percentage for BC1F1 and BC2F1 were 71.0% and 89.6%, respectively. Eventually, six best rice lines in BC2F1 population were identified to carry root trait genes for drought tolerance. The lines were closely related to the recurrent parent by having the highest recovery percentage and approximately similar phenotypic appearance. Hence, the development of drought tolerance rice lines through marker-assisted backcross breeding was believed to help the researchers in understanding the importance of molecular markers in enhancing the ability of rice crop towards biotic and abiotic constraints and accelerating the development of new varieties.